Theory of Cryptography 9th Theory of Cryptography Conference, TCC 2012, Taormina, Sicily, Italy, March 19-21, 2012. Proceedings - Cramer, Ronald; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed proceedings of the 9th Theory of Cryptography Conference, TCC 2012, held in Taormina, Sicily, Italy, in March 2012. The 36 revised full papers presented were carefully reviewed and selected from 131 submissions. The papers are organized in topical sections on secure computation; (blind) signatures and threshold encryption; zero-knowledge and security models; leakage-resilience; hash functions; differential privacy; pseudorandomness; dedicated encryption; security amplification; resettable and parallel zero knowledge.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Coding theory; Computer software; Computer Science; Data Encryption; Computer Communication Networks; Systems and Data Security; Coding and Information Theory; Math Applications in Computer Science; Algorithm Analysis and Problem Complexity